2022
DOI: 10.1007/jhep12(2022)064
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced soft limits in de Sitter space

Abstract: In flat space, the scattering amplitudes of certain scalar effective field theories exhibit enhanced soft limits due to the presence of hidden symmetries. In this paper, we show that this phenomenon extends to wavefunction coefficients in de Sitter space. Using a representation in terms of boundary conformal generators acting on contact diagrams, we find that imposing enhanced soft limits fixes the masses and four-point couplings (including curvature corrections) in agreement with Lagrangians recently derived … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…However, some of the shift fields have known fully interacting extensions that preserve the shift symmetries in a non-trivial way. For example the k = 0, 1, 2 scalars lead to AdS versions of the pion chiral Lagrangian, DBI, and special galileon, respectively [10,60,61]. Another example is the self-interacting spin 1, k = 0 theory [62,63], which was found in the massless, fixed curvature decoupling limit of various ghost-free interacting theories for a massive graviton [64] on AdS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some of the shift fields have known fully interacting extensions that preserve the shift symmetries in a non-trivial way. For example the k = 0, 1, 2 scalars lead to AdS versions of the pion chiral Lagrangian, DBI, and special galileon, respectively [10,60,61]. Another example is the self-interacting spin 1, k = 0 theory [62,63], which was found in the massless, fixed curvature decoupling limit of various ghost-free interacting theories for a massive graviton [64] on AdS.…”
Section: Discussionmentioning
confidence: 99%
“…This naturally leads to the question of what the analogous properties of shift symmetric theories in other spacetimes are. In dS, it was recently demonstrated that, at least at the lowest few orders in powers of the fields, the momentum space boundary wavefunction coefficients of the exceptional theories satisfy soft theorems that can be used to bootstrap the theories [61] (see also [67] for the flat space version, and [68][69][70] for earlier studies of soft limits of inflationary correlators). It would be interesting to study the higher point correlators of the CFT duals to the interacting exceptional theories in AdS, and to see how the non-linear shift symmetry manifests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft theorems also provide a useful organizing principle by which to classify effective field theories from the on-shell perspective. Field theories with enhanced symmetries lead to enhanced Adler zeroes of scattering amplitudes [10][11][12][13], and their corresponding wavefunction coefficients satisfy particular Ward identities [16,17].…”
Section: Jhep02(2023)123mentioning
confidence: 99%
“…where the ellipsis represents terms involving two or more ζs. 17 Translating into the notation of section 2, we have…”
Section: Jhep02(2023)123mentioning
confidence: 99%